Viruses as anticancer drugs - Russell, Stephen J.; Peng, Kah-Whye (Trends in pharmacological sciences (Regular ed.), 2007)
Oncolytic viruses are being developed as anticancer drugs. They propagate selectively in tumor tissue and destroy it without causing excessive damage to normal non-cancerous tissues. When used as drugs, they must meet stringent criteria for safety and efficacy and be amenable to pharmacological study in human subjects. Specificity for neoplastic tissue is the key to safety, and this goal can be achieved through a variety of ingenious virus-engineering strategies. Antiviral immunity remains a significant barrier to the clinical efficacy of oncolytic viruses but this is being addressed by using novel immune-evasive delivery strategies and immunosuppressive drugs. Noninvasive pharmacokinetic monitoring is facilitated by engineering marker genes into the viral genome. Clinical data on the pharmacokinetics of oncolytic viruses will be the key to accelerating their development and approval as effective anticancer drugs. This review introduces concepts relevant to the use of viruses as anticancer drugs, emphasizing targeting mechanisms as well as safety and efficacy issues that are currently limiting their clinical success.